Evaluation of fracture risk and potential drug holidays for postmenopausal women on long-term bisphosphonate therapy - Kostoff MD; Saseen JJ; Borgelt LM (Dove Medical Press, 2014)
Matthew D Kostoff, Joseph J Saseen, Laura M BorgeltDepartments of Clinical Pharmacy and Family Medicine, University of Colorado Skaggs School of Pharmacy and Pharmaceutical Sciences and School of Medicine, Aurora, CO, USAStudy objective: To describe characteristics of postmenopausal women on long-term bisphosphonate therapy who fall into one of four fracture risk categories (low, mild, moderate, high), and to determine the prevalence of women eligible for a drug holiday.Design: Retrospective electronic health record review.Setting: Eight primary care clinics within a university-based health care system.Patients: A total of 201 postmenopausal women of ages 55–89 years, with osteopenia or osteoporosis, prescribed bisphosphonate therapy for >4 years, between October 10, 2002 and September 9, 2012.Main results: The patients' mean age was 71.4 (±8.2) years; their mean body mass index was 25.3 (±5.6) kg/m2; and 73.1% were white. Seventy-four out of 201 patients (36.8%) were low-risk; 10/201 (5.0%) were mild-risk; 72/201 (35.8%) were moderate-risk; and 45/201 (22.4%) were high-risk. Eighty-one women (40.3%) were eligible for a drug holiday or discontinuation. The estimated drug cost avoided per eligible patient was $574.80. Calcium and/or vitamin D supplementation was documented in 52.7% of women.Conclusion: More than one-third of postmenopausal women taking long-term bisphosphonate therapy had low fracture risk, and over 40% of our patients were eligble for a drug holiday or discontinuation. These data emphasize the need to accurately assess risk and benefit in patients treated with bisphosphonate therapy.Keywords: postmenopausal osteoporosis, bisphosphonates, drug holiday, fracture